Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, Sanksi Pajak, Sosialisasi Perpajakan Dan Penerapan Sistem E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Fahria Alting; Suwito Suwito; Fitriani Sardju (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The objectives of this study are: To analyze the effect of tax knowledge, taxpayer awareness, tax Sanctions, tax socialization, and the application of the E-Samsat system on motor vehicle taxpayer compliance. The population used in this study were all motor vehicle taxpayers registered with the Ternate city Samsat for the 2018-20223 period. Sample withdrawal based on accidental sampling. The type of data used in this study is quantitative data and data analysis using the SPSS 29 application. The method used is Multiple Linear Regression Analysis. The results of this study indicate that Tax Knowledge, Taxpayer Awareness, Taxation Socialization have no effect on motor vehicle taxpayer compliance, while Tax Sanctions and Implementation of the E-Samsat System have a positive effect on Motor Vehicle Taxpayer Compliance at Samsat Ternate City.